A Metaphor Analysis Study Related to STEM Subjects Based on Middle School Students’ Perceptions - Sahin Idin; Ismail Donmez (Journal of Education in Science, Environment and Health)
The aim of this study is to determine what metaphors seventh and eighth grade students have when they identify STEM subjects. For this purpose, a form was developed to provide students to write their own metaphors related to STEM subjects. Qualitative research method was used and this research was conducted as a phenomenological study. 94 seventh and eighth grade students participated in this study from two different middle schools, which are located in the center of Ankara, Turkey. Students were encouraged to write their metaphors to identify STEM subjects. It has been seen that both seventh and eighth grade students had complexity while they were identifying science and technology subjects. Students used technology metaphor eleven times while they identified science, and they used science metaphor five times while they identified technology. It has also been learnt from students’ metaphors that students have not had enough information on math and engineering since the metaphors could not explain these subjects. It is recommended that some courses might be given to students within STEM subjects to provide them to learn those subjects.